Influence of Atrazine and Diclofenac Co-exposure on Hypothalamic-Pituitary-Testicular Axis Function in Rats (2021)
Humans and animals are commonly exposed to numerous chemicals through diverse sources causing unpredictable real-life health effects. This study evaluated the influence of joint exposure to the herbicide atrazine (ATZ) and the NSAID diclofenac (DCF) on the hypothalamic-pituitary-testicular axis function in pubertal rats. The animals were jointly exposed to ATZ (20 and 40 mg/kg body weight) and DCF (10 and 20 mg/kg body weight) for 42 days. In comparison with individual exposures, the current data illustrated that combined exposure to ATZ and DCF exacerbated the reductions in follicle stimulating hormone (FSH), luteinizing hormone (LH), serum and intra-testicular testosterone levels with testosterone/LH ratio. Additionally, co- exposure to ATZ and DCF worsened the sperm quality and quantity with marked disruption in the testicular function marker enzymes activities. The diminution in the epididymal, testicular and hypothalamic antioxidant defense mechanisms was intensified in animals co-exposed to ATZ and DCF. Moreover, the induction of reactive oxygen and nitrogen species, lipid peroxidation, inflammatory stress and histopathological lesions in the epididymal, testicular and hypothalamic tissues was intensified in co-exposed animals. These data accentuate the possible male reproductive dysfunction related to ATZ and DCF co-exposure in mammals and, by extension, provide useful insights into the public health threats associated with combined exposure to pesticides and pharmaceuticals.